Infection phase‐dependent dynamics of the viral and host N6‐methyladenosine epitranscriptome in the lifecycle of an oncogenic virus in vivo. Issue 1 (28th November 2022) - Zhuang, Guoqing; Zhao, Xuyang; Jin, Jiaxin; Zhu, Xiaojing; Wang, Rui; Zhai, Yunyun; Lu, Wenlong; Liao, Yifei; Teng, Man; Yao, Yongxiu; Nair, Venugopal; Yao, Wen; et al.
Abstract: Dynamic alteration of the epitranscriptome exerts regulatory effects on the lifecycle of oncogenic viruses in vitro. However, little is known about these effects in vivo because of the general lack of suitable animal infection models of these viruses. Using a model of rapid‐onset Marek's disease lymphoma in chickens, we investigated changes in viral and host messenger RNA (mRNA) N6‐methyladenosine (m 6 A) modification during Marek's disease virus (MDV) infection in vivo. We found that the expression of major epitranscriptomic proteins varies among viral infection phases, reprogramming both the viral and the host epitranscriptomes. Specifically, the methyltransferase‐like 3 (METTL3)/14 complex was suppressed during the lytic and reactivation phases of the MDV lifecycle, whereas its expression was increased during the latent phase and in MDV‐induced tumors. METTL3/14 overexpression inhibits, whereas METTL3/14 knockdown enhances, MDV gene expression and replication. These findings reveal the dynamic features of the mRNA m 6 A modification program during viral replication in vivo, especially in relation to key pathways involved in tumorigenesis.